The Mystical Element in Paul's Theology of the Holy Spirit: An African Interpretation - Ejenobo, David T. (Asia Journal of Theology, 2009)
The article examines three passages from the theology of Paul the Apostle which aims to help understand the mystical element in his concept of the Holy Spirit. It asks what is the nexus of all of Paul's writings on the Holy Spirit which leads itself to more interpretation. The article seeks to interpret Paul's theology with a view to use it as pegs to hang evangelistic works in the African continent.
Free
Keywords: AFRICA; EVANGELISTIC work; HOLY Spirit; PAUL; the Apostle; Saint; THEOLOGY